PERAN PENDAMPINGAN BELAJAR DALAM MENGEMBANGKAN LITERASI DAN NUMERASI ABAD 21 ANAK PANTI ASUHAN: TINJAUAN LITERATUR SISTEMATIS - Yusyrotur Rodliyah; Siti Faizah; Riska Pristiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning assistance is an essential form of facilitation that helps children overcome learning difficulties, particularly children in orphanages with diverse social backgrounds, traumatic experiences, and varying cognitive abilities. The lack of reading habits and the low culture of literacy and numeracy among children in orphanages indicate the need for structured interventions through learning assistance programs oriented toward literacy and numeracy development. This study aims to systematically analyze the role of learning assistance in developing literacy and numeracy among children in orphanages. The research employs a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Data were obtained from national articles indexed in Google Scholar and published between 2022 and 2026. The findings show that structured, empathetic, and continuous learning assistance has a significant impact on improving reading, numeracy, writing, critical thinking skills, and learning motivation among children in orphanages. Furthermore, the integration of digital-based approaches, creative activities, and community collaboration effectively strengthens the sustainability and inclusivity of literacy and numeracy programs within orphanage environments. This study concludes that learning assistance is not merely an academic effort but also a form of social empowerment that supports the development of a sustainable literacy and numeracy culture within the framework of 21st-century learning.